The Clinical Impact of Immediate on-Site Cytopathology Evaluation During Endoscopic Ultrasound-Guided Fine Needle Aspiration (EUS-FNA) of Pancreatic Mass - Azar, Riad R. (2014)
Observational data on the impact of an on-site cytopathologist (CyP) during EUS-FNA of pancreatic masses have reported conflicting results regarding diagnostic yield.